Answers

  • Brainly User
2014-09-09T22:17:54+05:30
Use the identity a³ + b³ + c³ - 3abc = (a+b+c)(a²+b²+c² - ab - bc - ca)

In your question, a = 4x, b = 5y, c = -4z
Substituting these in above identity,
(4x)³ + (5y)³ + (-4z)³  - 3X(4x)(5y)(-4z) =
(4x+5y-4z)(16x² + 25y² + 16z² - 20xy + 20yz + 16zx)
0
The Brainliest Answer!
2014-09-10T19:35:41+05:30
A³+b³+c³-3abc=(a+b+c)(a²+b²+c²-ab-bc-ca)
so, (4x)³ + (5y)³ + (-4z)³ - 3X(4x)(5y)(-4z)
= (4x+5y-4z)(16x² + 25y² + 16z² - 20xy + 20yz + 16zx)
1 5 1
I hope it will help you.
thnq
My Pleasure.